Progress, problems and prospects of livestock pluripotent stem cells - Yadav C.B.; Verma V.; Tabassum N.; Kumar M.; Kumar A.; Bajpeyee A.K.; Dwivedi S.; Singh M.P.; Singh A.K. (My University, 2025)
Pluripotent Stem (PS) cells are the unicellular equivalent to the whole animal. Under the right culture conditions they are capable of giving rise to all cell types of an adult animal. They also facilitate complex genetic modifications as they are more acquiescent to homologous recombination and divide indefinitely in culture. However, PSCs (Pluripotent stem cells) are only available in rodents (mouse, rat) and primates (monkey, human). Livestock stem cells provide a more suitable model for studying human diseases than their rodent counter parts. Pig (Sus scrofa) in particular, is an excellent model for cardiovascular disease research. Pluripotent stem cells (PSCs) generated from pigs provide significant clinical insights for cardiac cell therapy. However, more often than not Inner Cell Mass (ICM) retrieved from livestock embryos could not reach a pluripotent state as they cannot give rise to chimeras. Advances in stem cell technology, innovative cell culturing and induced pluripotency to generate stem cells has radically transformed the basic and applied investigations and applications of livestock stem cells. © 2017 Nova Science Publishers, Inc.